Application of Interactive Website-Based Deep Learning Approach to Improve Indonesian Learning Outcomes in Elementary Schools - Sulistyowati, Prihatin; Maulani, Rizhi Ahbar; Suswati, Hermin (Sistem-Among : Jurnal Pendidikan Sekolah Dasar, 2025)
This research is a Classroom Action Research which aims to improve the Indonesian learning outcomes of grade II elementary school students through the application of an interactive website-based Deep Learning approach. The background of this study is the low literacy skills and limited variation in digital-based learning media in Indonesian language learning, which tend to make students passive and less motivated. This study was carried out in two cycles involving 28 students, with each cycle consisting of the stages of planning, implementation, observation, and reflection. Data were collected through learning outcome tests and observation of student learning activities during the learning process. The results showed a significant improvement in learning completeness, from 32.14% in the pre-cycle to 75% in the second cycle, accompanied by an increase in the average student score from the low category to the good category. Furthermore, the effect size of improved learning outcomes was calculated at 1.23, which falls into the large category, indicating a strong and meaningful impact of the intervention on students' cognitive achievements. The application of interactive website-based media in this research succeeded in encouraging students to be more actively involved, facilitating meaningful understanding, and creating a more enjoyable and interactive learning atmosphere. Theoretically, this research contributes to the development of Deep Learning-based digital learning models for early literacy in elementary schools, an area that is still relatively limited in Indonesian language education.